Preparation of Some Oxygenic Compounds and Comparing Their Antibacterial Activity with Pomegranate Puniea granatum Peels Extracts - Hamad Shehab AL-Obaidi, Omar; Faraj Hamadi Al-Hiti, Waleed; Jasir Mohammed AL-Rawi, Bilal; Mahdi Turky, Bushra; Hussein Kshash, Abdullah; Salih Mohammed, Aeed; Oday Ezzat, Mohammed (Asian Journal of Chemistry, 2012)
The aim of this study is to prepare and identify a group of oxygenic compounds and compare their antibacterial and antitumor activity with pomegranate peels extracts. Twenty oxygenic compounds were identified as a chalcones. While pomegranate peels extracts divided into cold distilled water extracts, hot distilled water extracts, ethanol extracts and methanol extracts. Statistical analysis used was one way ANOVA. The results indicated that the oxygenic compounds in 10-3 M concentration gave antibacterial activity against E. coli and Staphylococcus aureus (p < 0.001). The extracts inhibited the bacteria growth in order (EtOH < MeOH < H2O) (p < 0.001).